2009
DOI: 10.3899/jrheum.081160
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Genetic Association and Interaction Between the TYK2 and IRF5 Genes in Systemic Lupus Erythematosus

Abstract: The IFN pathway genes IRF5 and TYK2 may act epistatically in increasing risk for SLE, but our lack of replication does not exclude effects of the other genes studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 45 publications
2
60
1
Order By: Relevance
“…Interestingly, one rare MSassociated variant (rs34536443) is considered to be protective, whereas another (rs55762744) was recently identified as a risk allele (17). rs12720356, initially reported to be protective in SLE (13), was not confirmed in a replication study (12) and instead found to be a risk allele in Crohn's disease (20,22). A frequent variant (rs2304256) has been shown to be protective in SLE, Crohn's, and type 1 diabetes in European populations (Table I).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, one rare MSassociated variant (rs34536443) is considered to be protective, whereas another (rs55762744) was recently identified as a risk allele (17). rs12720356, initially reported to be protective in SLE (13), was not confirmed in a replication study (12) and instead found to be a risk allele in Crohn's disease (20,22). A frequent variant (rs2304256) has been shown to be protective in SLE, Crohn's, and type 1 diabetes in European populations (Table I).…”
mentioning
confidence: 85%
“…Many SNPs are in the coding region, and .100 nonsynonymous variants have been annotated. Genome-wide association studies and more targeted candidate approaches have shown strong linkage of Tyk2 haplotypes or individual SNPs to systemic and organ-specific autoimmune diseases, namely systemic lupus erythematosus (SLE) (11)(12)(13)(14), multiple sclerosis (MS) (15)(16)(17)(18)(19), Crohn's disease (20)(21)(22), psoriasis (23), type 1 diabetes (24), endometriosis-related infertility (25), and primary biliary cirrhosis (26) (Table I). Interestingly, one rare MSassociated variant (rs34536443) is considered to be protective, whereas another (rs55762744) was recently identified as a risk allele (17).…”
mentioning
confidence: 99%
“…We read with interest the study of Hellquist, et al 1 showing tyrosine kinase 2 (TYK2) is associated with systemic lupus erythematosus (SLE). Similar results have been reported in different Caucasian populations 2,3,4 , but not in a recently published Japanese study 5 .…”
Section: To the Editormentioning
confidence: 99%
“…We read with interest the letter of Suarez-Gestal, et al 1 , and we believe that it is useful to briefly discuss possible causes of differences between our study 2 , which reported an interaction between the TYK2 and IRF5 genes, and the report of Suarez-Gestal, et al It is a common observation that replicating even single-gene association results in complex disorders is not always easy, and largely the same causes that may explain these differences also apply to gene-gene interaction studies.…”
Section: To the Editormentioning
confidence: 97%
“…Both our smaller study 2 and that of Suarez-Gestal, et al 1 would undoubtedly have benefited from larger sample sets. Our patients may have included a larger proportion of cases ascertained for systemic lupus erythematosus (SLE) through their skin symptoms, as many of our patients were recruited through dermatology services.…”
Section: To the Editormentioning
confidence: 97%